ANALISIS TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH BERBASIS WEBSITE PADA PEMERINTAH KABUPATEN/KOTA PROVINSI SULAWESI UTARA - Rafael, Kevin; Gamaliel, Hendrik; Korompis, Claudia W. M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2024)
Transparency is a key element in efforts towards good governance, especially in the context of corruption prevention and increased public participation. Although regulations mandate increased transparency, previous research indicates that its implementation is still suboptimal, particularly in budget information provision. Therefore, this study focuses on measuring transparency based on availability, accessibility, timeliness, and frequency of disclosure of local financial management information. The method used refers to the Open Budget Index designed by the International Budget Partnership. In contrast to previous research, this study specifically examines transparency in each websites Regency/City in North Sulawesi Province in the years 2021–2022.